DEVELOPMENT OF LOCAL ENTREPRENEURSHIP. CASE OF BIALOGARD COUNTY (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article presents the issues concerning the development of local entrepreneur-ship. The main objective of this paper is to analyze and evaluate the development of entrepreneurship in the district Bialogard between 2004-2012. The analysis of data taken from GUS and BDL.
Keywords: entrepreneurship, enterprise, industry, business, development